The establishment of a new major moulting site for Greylag Geese Anser anser at Lake Hornborgasjön, southern Sweden - Nilsson, Leif; Hermansson, Clas (Wildfowl, 2019)
At around 1900, Lake Hornborga in southern Sweden was considered to be one of the best breeding lakes for waterbirds in the country. In subsequent years, the area was drained and lake water levels reduced to avoid flooding and obtain land for farming. By 1950, the remaining lake and wetland area (34 km2) had become a swamp, totally overgrown with reed beds and bushes. The Swedish Environmental Protection Agency initiated a lake restoration project during the 1960s and 1970s and by 1995 the site had been restored to a shallow lake. Greylag Geese Anser anser started using the lake for breeding and moulting shortly thereafter, and it has attracted increasing numbers of moult migrants over the last 15 years, with 28,000 moulting geese counted in 2015. Neck-banding and collar resightings during 2004–2007 showed that the lake attracted geese not only from south Sweden and Denmark but also from eastern continental Europe (e.g. Poland) to moult. Seventy-two Greylag Geese marked at a study area in Scania, southwest Sweden, have been seen moulting at Lake Hornborgasjön, whereas geese from this area formerly moulted mainly in Flevoland in the Netherlands and later in Denmark. Individual birds from other areas were also shown to have changed their moulting sites in recent years.